2007
DOI: 10.1007/s10439-007-9269-y
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-driven Hypothesis with Gene Ontology (GO) Analysis

Abstract: Abstract-Most of the genes are under selective pressure to maintain their expression levels in the tissues. In a recent study, we have proposed a ''tissue-driven'' hypothesis stating that the stabilizing constraints on gene expression levels can be partitioned among tissues; tissues differ in their tolerance to gene expression variances; and the constraints on expression divergence is correlated with the constraints on sequence divergence. Here we further tested the ''tissue-driven'' hypothesis by sub-grouping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In particular, we discuss in some details about the translational selection hypothesis [12-14]. This theory demonstrates that one of major components in the functional constraint imposed in the protein sequence is the minimization of misfolding burden, or the sequence requirement to retain the capability to fold into the correct, functional protein structure.…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…In particular, we discuss in some details about the translational selection hypothesis [12-14]. This theory demonstrates that one of major components in the functional constraint imposed in the protein sequence is the minimization of misfolding burden, or the sequence requirement to retain the capability to fold into the correct, functional protein structure.…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…We also find that mRNA expression abundance contributes significantly to some but not all properties. Interestingly, expression level is correlated with expression breadth [18], but not with phyletic age; under our hypothesis, the observed result suggests that ancient cellular functions do not generally require large protein numbers, but that expression levels are rather driven by tissue-specific effects [9]. …”
Section: Resultsmentioning
confidence: 97%
“…The duplication thus creates two gene copies with the same phyletic age, but very different expression profiles [7,8]; other changes of gene attributes (e.g., sequence changes to optimize tissue-specific function) might follow. Furthermore, genes expressed in different tissues may be under different constraints, resulting in variable evolutionary rates across proteins with similar expression breadth [9]. Another important factor known to influence gene structure and evolution is expression abundance [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Neural tissues developed from ectoderm were the most conserved sub-group. The expression pattern of genes in these tissues is more conservative to each other: more conserved individual genes, more conserved GO modules, less differentially expressed GO modules and more significantly correlated GO modules, compared with tissues developed from mesendoderm [8]. Notably, tissues developed from endoderm appear to have a large number of differentially expressed genes, which might be related to the large functional variation of these tissues and the long developing time in embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies showed that different tissues shared a large number of ubiquitously expressed genes and the tissue specific genes are more likely to reveal tissue-specific function. A gene set (Gene Ontology - GO) based analysis proposed a “tissue-driven” hypothesis which describes the relationship between the stabilizing constraints on tissue-specific gene expression and individual GO categories [8]. …”
Section: Introductionmentioning
confidence: 99%